The Effect of Bovine Viral Diarrhoea Virus Biotypes on Bovine Oocyte In Vitro - Amirmahdi Roshanzamir; Massoud Talebkhan Garoussi; Jalil Mehrzad (Veterinary Medicine and Science)
ABSTRACT Bovine viral diarrhoea virus (BVDV) is a significant pathogen in the global cattle population, with two biotypes: cytopathic (CP) and non‐cytopathic (NCP), differing in their effects on cell culture. This study aimed to examine the impact of BVDV on the expression of apoptosis‐related genes and total antioxidant capacity (TAC) in vitro. Oocytes were obtained from post‐slaughter bovine ovaries and infected with both BVDV biotypes in vitro. Gene expression levels of bcl 2, bax, caspase 3 and caspase 9 were assessed using reverse transcription‐quantitative PCR (RT‐qPCR). The results indicated significant differences in gene expression levels, with bcl 2 expression reduced in CP and NCP‐infected oocytes compared to the control group (p < 0.05). Additionally, bax and caspase 3 expression levels were significantly elevated in the CP BVDV groups (p < 0.05). In the NCP BVDV groups, the expression of bcl 2 decreased (p < 0.05), while caspase 9 expression increased by 3.588‐fold compared to the control group (p < 0.05). Furthermore, TAC levels in the CP groups were significantly lower than those in the control group (p < 0.05). These findings suggest that the CP biotype of BVDV markedly affects TAC and alters the expression of key apoptosis‐related genes, while the NCP biotype reduces bcl 2 expression and increases caspase 9 expression.